Equity valuation : Verbund AG - Popp, Benedikt (2014)
The purpose of this report is to determine the equity value of the Austrian company Verbund. For this reason, first the appropriate methods are defined in the Literature Review, followed by the valuation of the company through the use of the DCF model. Additionally, the multiple approach is used as a supplement. The obtained results show a considerable undervaluation of Verbund. The thereby calculated fair value per share is further tested for its risk exposure to a change in certain variables, by conducting a Sensitivity Analysis. Moreover, the estimated share price is compared to the suggested price of a leading Investment Bank. The identified discrepancies are explained by the use of different valuation methods.